2009
DOI: 10.2136/sssaj2008.0285
|View full text |Cite
|
Sign up to set email alerts
|

Cation Exchange Selectivity Coefficient Values on Smectite and Mixed‐Layer Illite/Smectite Minerals

Abstract: Sodium‐K, Na‐Ca, Na‐Mg, and Na‐Sr exchange isotherms were performed at a total Cl concentration of about 0.005 mol L−1 on the fine fraction (<2 μm) of MX80 montmorillonite, mixed‐layer illite smectite minerals (IS), and clayey stones from European underground research laboratories. The derived selectivity coefficients for Na‐K, Na‐Ca, Na‐Mg, and Na‐Sr were found to vary very significantly as a function of the exchanger composition. A model was built to reproduce the data, taking into account the change of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 51 publications
3
51
1
Order By: Relevance
“…The cation exchanger composition estimated in equivalent fraction with the model of Tournassat et al (2009a) amounted to 18, 56 and 23% for Na, Ca and Mg, respectively. A low content of K was not considered in the calculation.…”
Section: Methodsmentioning
confidence: 97%
“…The cation exchanger composition estimated in equivalent fraction with the model of Tournassat et al (2009a) amounted to 18, 56 and 23% for Na, Ca and Mg, respectively. A low content of K was not considered in the calculation.…”
Section: Methodsmentioning
confidence: 97%
“…The model considers ion exchange on illite and smectite represented by the selectivity exchange coefficients on the two exchangers [42,43].…”
Section: Callovian-oxfordian Claystone Modelmentioning
confidence: 99%
“…The ion exchange composition on the claystone was initially equilibrated with the COx pore water shown in Table 4. The selectivity coefficients available in Table 9 were calculated using exchange models given by Tournassat et al [42,43]. The coefficients are based on the Gaines and Thomas convention [50,51].…”
Section: Ion Exchangementioning
confidence: 99%
“…Analyses of cation exchange populations were performed on whole rock samples using the cobalt hexamine method (Rémy and Orsini, 1976;Ciesielski and Sterckeman, 1997) as previously described by Gaucher et al (2004Gaucher et al ( , 2006 and Tournassat et al (2007Tournassat et al ( , 2008Tournassat et al ( , 2009. Experimental tests showed that carbonate minerals and sulphate minerals (e.g.…”
Section: Determinations Of Cation Exchange Populations and Cation Excmentioning
confidence: 99%